Divergência genética, adaptabilidade e estabilidade produtiva de genótipos de soja sob infecção natural por ferrugem, sem fungicida - Silva, Nathalia Salgado (2018)
Studying a genetic diversity, adaptability and stability of soybean genotypes are of extreme importance for breeding programs, since the identification of parents is impaired by the narrow genetic base of Brazilian soybean, and a recommendation of cultivars for the different regions is one of the main challenges for improvement. This dissertation is subdivided into three chapters, the first is the theoretical reference of soy, economic importance, genetic breeding and Asian rust. The second chapter was developed with the objective of evaluating the genetic divergence of soybean genotypes under natural rust infection. The experiment was carried out at Fazenda Capim Branco, UFU, in the 2016/17 harvest. A total of 14 genotypes were used, including 10 lines developed by the UFU Soybean Breeding Program and four cultivars (UFUS 7415, UFUS Riqueza, TMG 801 and BRSGO 7560) in a randomized complete block design with three replicates. It was concluded that there is genetic variability for all agronomic traits, except for the height of the first pod and plant height at flowering. The lineages UFUS 1117-01, UFUS 1117-07, UFUS 1117-08, UFUS 1117-09, UFUS 1117-10 presented resistance to Phakopsora pachyrhizi and were identified in components of plant height at maturity, number of pods, number of days to maturity and area under disease progress curve they were the ones that contributed most to a genetic divergence. Hybridizations were suggested aiming the resistance to Asian rust, the strain UFUS 1117-06 was present in all crosses. The third chapter refers to the study of the adaptability and productive stability of the 14 soybean genotypes grown in the 2013/14, 2014/15, 2015/16, 2016/17 seasons. It was possible to conclude that the genotypesenvironments interaction is of a complex type for grain yield. UFUS 1117-01 lineage was identified as being of high stability produced by the methods of Eberhart and Russel (1966), Wricke (1965), Principal additive effects and multiplicative interaction (AMMI 1 and AMMI 2), and Centroid. UFUS 1117-07 genotype showed high stability by the methods Eberhart and Russel (1966), Wricke (1965), Lin and Binns 1988 modified by Carneiro 1999 and wide adaptability by Eberhart and Russel and Centroid. UFUS 1117-09 was identified as being adaptive to unfavorable environments by Lin and Binns modified by Carneiro, AMMI1 and Centroid, while UFUS 1117-10 presented adaptability to environments favorable to AMMI1 and Centroid and high stability by Eberhart and Russel.